Prediction of Corona anxiety based on personality characteristics and self-discipline in vaccinated people at the vaccination center of the Prophet’s (PBUH) complex - Borminejad, Leila; Banisi, Parinaz; Barkhordari, Fatemeh; Haghani, Shima; Farhadi Afshar, Parnian; Jalilzadeh, Mahdieh; Delfanazari, Ghanbarali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The rapid spread and epidemic, its high mortality rate and the absence of any definite and approved treatment and medicine for Corona have caused severe disorders. The aim of the current research was to predict corona anxiety based on the personality characteristics of self-care in vaccinated people at the vaccination center. Method: The method of the current research is quantitative and has been implemented in a descriptive-correlational way, and it is practical in terms of the purpose of this research. The study population of this research is all the people who visited the vaccination center of the Holy Prophet (PBUH) Complex of West Tehran Azad University in the Fall 2021. Among these people, 400 vaccinated people who received the second dose were selected as a sample based on the amount calculated by Gpower software in a simple random manner. Personality, self-diagnosis and corona anxiety tests were taken from the subject. The data were analyzed using the statistical method SEM. Results: The results show that Corona anxiety is predicted based on personality traits and self-diagnosis. The path coefficient of neuroticism (P<0.001, β=0.419), extroversion (P=0.002, β=0.160) has a positive and significant effect on corona anxiety and flexibility (P<0.001), β=-0.23) and pleasantness (P<0.001, β=-0.332) have a significant and negative effect on Corona anxiety. Also, the path coefficient of the effect of responsibility on corona anxiety has no significant effect (P=0.464, β=0.036). The path coefficient of the effect of self-care on corona anxiety has a positive and significant effect (P<0.001, 290/ β = 0). Conclusion: During the corona virus epidemic, the media plays an active role in informing about the news and events caused by this epidemic. Therefore, these notifications will lead to high physiological stimulation and, as a result, negative emotions of people, which leads to people not being successful in regulating their emotions and increases self-morbidity. Accordingly, self-diagnosis is also associated with an increase in anxiety about Corona. Therefore, it is not far from the expectation that self-diagnosis predicts corona anxiety in vaccinated people.